Chiococca alba Snowberry: FPS124/FP124, 5/2007 - Gilman, Edward (EDIS, 2007)
This document serves as a comprehensive guide to the vibrant and diverse genus Celosia, detailing the cultivation and care of two prominent types: Celosia cristata, known for its unique crested flower heads, and Celosia plumosa, recognized by its feathery plumes. It outlines the plant’s growth habits, including height, spread, and leaf configuration, as well as the array of flower colors available. The guide provides practical advice on planting in various USDA hardiness zones, soil preferences, and managing common pests. It also introduces gardeners to notable Celosia cultivars and series, such as the compact ‘Jewel Box’ and ‘Kimono’ series, alongside the more statuesque ‘Floradale’ and ‘Castle’ series, aiding enthusiasts in selecting the right Celosia for their garden landscapes. Original publication date October 1999.